Differences In Knowledge Levels Before and After Dagusibu Counseling at Students Smk Swasta Arjuna Laguboti - Lestari, Meliani Dwi; Hutagaol, Sherly H.; Sirait, Wenni Elisabet (Institute of Accounting Research and Novation (IARN), 2025)
DAGUSIBU (Get, Use, Save, Throw Away) is a health education program created by the Indonesian Pharmacists Association in realizing the drug-aware family movement (GKSO) to improve the quality of life of the community so that they achieve a true level of health. The purpose of this study was to determine the Difference in Knowledge Level Before and After Dagusibu Counseling at Students SMK Swasta Arjuna Laguboti. The Research Design used in this study was Quasi Experimental Research, using the Total Sampling technique was 73 respondents. The results of this study before the counseling indicate have a sufficient level of knowledge as many as 61 respondents (83.6%) and have a good level of knowledge as many 12 respondents (16.4%). The results of the study after the counseling showed that all respondents 100% had a good level of knowledge. By using one sample T-Test test shows that t count = 49.553. T table is obtained with df = 72, sig 5% (1 tailed) = 1.666. Because -t table < from t count (-1.666 < 49.553), then Ho is accepted, meaning there is a difference in the level of knowledge before and after Dagusibu counseling at students SMK Swasta Arjuna Laguboti. The results of this study indicate that counseling has a significant impact on increasing knowledge. So it can be concluded that students SMK Swasta Laguboti experienced a good increase in knowledge after counseling in terms of obtaining, using, storing and disposing of drugs properly. The suggestion in this study is expected to be used as input to improve knowledge related to Dagusibu.